RUSSIAN-CHINESE HUMANITARIAN COOPERATION WITHIN THE SHANGHAI COOPERATION ORGANIZATION - Tsvyk, G.I. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Mezhdunarodnye otnosheni͡a, 2018)
The article is devoted to the development of Russian-Chinese humanitarian cooperation within the framework of the Shanghai Cooperation Organization. The author analyzes main aspects of humanitarian cooperation between the SCO member states, due to the fact that cooperation in this field is very important within the SCO’s agenda. At the same time, the special significance of Russian-Chinese relations in this sphere is highlighted in connection with the fact that Russia and China were the first among SCO member states to declare humanitarian cooperation. Since that time both countries were actively developing bilateral cooperation in various spheres. The article examines various spheres of humanitarian relations within the SCO, namely education, culture, academic mobility, sports and tourism. Recently, the humanitarian component has become increasingly important in Russian-Chinese cooperation, which in the last two decades has begun to include not only traditional spheres of interaction such as culture and education, but also health, sports, mass media and tourism. In addition, after the establishment of strategic partnership between the Russian Federation and the People's Republic of China, humanitarian cooperation, having received great state support, began to develop very fast. With the advent of a new international regional organization, which member-states are Russia, China, Kazakhstan, Kyrgyzstan, Turkmenistan, Uzbekistan, and since 2017, India and Pakistan, a new format of bilateral cooperation between Moscow and Beijing in the framework of the SCO has emerged.